Disease-specific Pay-for-Performance Programs: Do the P4P Effects Differ Between Diabetic Patients With and Without Multiple Chronic Conditions?. Issue 11 (November 2016) - Huang, Yu-Chin; Lee, Miaw-Chwen; Chou, Yiing-Jenq; Huang, Nicole
Abstract : Background: Several studies have investigated the effects of pay-for-performance (P4P) initiatives. However, little is known about whether patients with multiple chronic conditions (MCC) would benefit from P4P initiatives similarly to patients without MCC. Objectives: The objective of this study was to compare the effects of the diabetes mellitus pay-for-performance (DM-P4P) program on the quality of diabetic care between type 2 diabetic patients with and without MCC. Methods: This study used data from Taiwan's Longitudinal Health Insurance Database 2005. Of this cohort, 52, 276 diabetic patients were identified. To address potential selection bias between the intervention and comparison groups, the propensity score matching method was used. Generalized estimating equations were applied to analyze the difference-in-difference model to examine the effect of the intervention, the DM-P4P program. Results: The disease-specific DM-P4P program had positive impacts on process and outcome indicators of health care quality regardless of patients' MCC status. Diabetic patients with MCC experienced a significantly larger decrease in the admission rate of diabetes-related ambulatory care sensitive conditions after the P4P enrollment over time compared with patients without MCC. Conclusions: The positive impacts on use of diabetes-related services were comparable between diabetic patients with and without MCC. Most importantly, for MCC patients, the disease-specific DM-P4P program had a stronger positive impact on health outcomes. Hence, the commonly observed phenomenon of "cherry picking" in implementing P4P strategies may lead to disparities in the quality of diabetic care between diabetic patients with and without MCC. Abstract : Supplemental Digital Content is available in the text.